Pemetaan Topografi Teristris Berbasis Sistem Informasi Geografis Menggunakan â€œGps Handheldâ€ Sebagai Acuan Pencarian Koordinat Awal (Studi Kasus: â€œMasterplan Sport Centreâ€ Di Muntok, Bangka Belitung) - Rahman, Aris; Nasihien, Ronny Durrotun; Hardaningrum, Farida (Universitas Dr. Soetomo, 2019)
Sports activity today is very significant growth. The spirit to welcome the 2018 Asian Games, which was originally held in Jakarta and Palembang, made the West Bangka district government plan to build a Sport Center as a medium to foster youth activities and especially in sports. The selected location is in Air Belo Village, Muntok District, West Bangka Regency with 13 hectares area.The research of planning of Masterplan Sport Center by using Topographical Mapping Method Based on Geographic Information System (GIS) with initial coordinate reference using GPS Handheld is expected to produce accurate design that can meet the needs of sports facilities and tourism sector in West Bangka Regency.The result of the Topography Teristris measurement in the form of Contour Map integrated with Rambut Bumi Indonesia (RBI) resulted in the location oriented Thematic map. For position correction using Google Earth, the result must meet Gross coordinate position error fault